The Association Between Variability in Electrolytes and the In-Hospital Mortality in Critically Ill Children in Pediatric Intensive Care Units - Lin, Jilei; Zhang, Yin; Chen, Meng; Dai, Jihong; Song, Anchao; Chen, Jianchuan; Tao, Xingping (Frontiers in Pediatrics, 2021)
Objective: This study aimed to explore the association between the variability in electrolytes and the in-hospital mortality in critically ill children admitted into ICUs. Design: Retrospective case-control study. Setting and participants: A total of 11,245 children have been admitted to ICUs of Children’s Hospital of Zhejiang University from 2010 to 2018. Methods: The coefficient of variation (CV), standard deviation(SD), and variability independent of the mean(VIM) were calculated as variability indices. High variability was defined as having values in the highest quartile for each parameter. Age, sex, diagnoses of disease and surgical treatment were adjusted in the multivariable-adjusted logistic regression model. Results: A total of 11,245 children were included, and 660 patients died in hospital. The median(P25, P75) potassium, sodium and chloride of all patients were 3.8(3.58, 4.09), 136.83(135.11, 138.60), and 108.67(105.71, 111.17), respectively. The U-shaped relationships between the mean, lowest and highest levels of potassium, sodium and chloride and the in-hospital mortality were observed. The lowest mortality was noted when serum potassium, sodium and chloride was between approximately 3.5 to 5.0 mmol/l, 135 to 145 mmol/l and 105 to 115 mmol/l, respectively. The area under the curve (AUCs) of 3 indices of variability in electrolytes were larger than those of mean, lowest levels of electrolytes in predicting the in-hospital mortality. In the multivariable adjusted model, the odds ratios and 95% CI of the in-hospital mortality were 3.14 (2.44-4.04) for one parameter, 5.85 (4.54-7.53) for two parameters, and 10.32 (7.81-13.64) for three parameters compared with subjects having no parameters of high variability measured as the CV. The results were consistent when the variability was determined using the SD and VIM (all P for trend<0.001). Consistent results were noted in various subgroup analyses. Conclusions: This study showed that individuals with higher variability of each parameter were related with higher risk of in-hospital mortality. There was a linear association between the number of high variability parameters and the in-hospital mortality. The variability of electrolytes might be a good predictor for in-hospital mortality of children in ICUs.